Occupational Health and Safety Risk Assessment in Mechanized Waste Processing Operations Using Failure Mode and Effect Analysis - Ulfa Alfiani Nadillah; Mila Tejamaya; Annisa Dwi Safiyanti (Tecno Scientifica Publishing, 2026)
Mechanized waste processing facilities present elevated occupational safety risks due to intensive interaction between workers and rotating machinery. This study assessed occupational safety risks in the mechanized sorting, shredding, and compaction stages at an Integrated Solid Waste Treatment Facility (TPST X) producing Refuse-Derived Fuel (RDF) in Cimahi City, Indonesia, using the Failure Mode and Effect Analysis (FMEA) technique. Employing a descriptive analytical study design, data were collected through direct observation, in-depth interviews with 24 informants, and document review. Failure modes were identified for each machine-based process, and Risk Priority Numbers (RPN) were calculated from the product of severity, occurrence, and detection scores. A total of 37 failure modes were identified across eight machine categories: conveyor systems, magnetic separator, turbo separator, gibrik, shredder, centris, crusher, and ball press. Four failure modes were classified as very high risk (RPN ≥ 181), with the three highest values (RPN = 240 each) associated with noise exposure in the turbo separator, gibrik, and centris work areas.